Designation of soap molder machine and procedure for transparent soap - Mat Sharif, Zainon; Mohd Taib, Norhasnina; Yusof, Mohd Sallehuddin; Rahim, Mohammad Zulafif; Mohd Tobi, Abdul Latif; Othman, Mohd Syafiq (IOP Publishing, 2017)
Transparent soap is actually the combination of actual soap and solvent. The solvent is added into the soap solution to produce the transparent characteristic. The problem from the previous production is that tiny air bubbles were observed inside the soap resulted in less attractive appearance. Current method of producing the soap bar had taken more than 8 hours and having difficulties to take out the soap bar from the plastic mold with low production rate. It is expected that the air bubble problem can be solved using this new soup molder machine. The soap production rate is believed to increase with the invention of soap molder machine. By reducing the production time from 8 hours to 2 hours, it improve production rate significantly.